In vitro activity of colistin as single agent and in combination with antifungals against filamentous fungi occurring in patients with cystic fibrosis. Issue 3 (22nd November 2012) - Schemuth, H.; Dittmer, S.; Lackner, M.; Sedlacek, L.; Hamprecht, A.; Steinmann, E.; Buer, J.; Rath, P.‐M.; Steinmann, J.
Summary Because published reports indicate that the antibiotic colistin (COL) has antifungal properties, this study investigated the antifungal in vitro activity of COL as single agent and in combination with the antifungal compounds voriconazole (VRC), caspofungin (CAS) and amphotericin B (AMB) against Scedosporium/Pseudallescheria spp., Exophiala dermatitidis and Geosmithia argillacea. In total, susceptibility was determined for 77 Scedosporium/Pseudallescheria spp., 82 E. dermatitidis and 17 G. argillacea isolates. The minimal inhibitory concentrations (MICs) of COL and the antifungals as single compound and in combination were determined with MIC test strips. Drug interactions were detected by crossing the MIC test strips at a 90º angle. The fractional inhibitory concentration index was used to categorise the drugs' interaction. The MIC50 value of COL was 12 μg ml−1 for S. prolificans, 16 μg ml−1 for P. apiosperma, 16 μg ml−1 for P. boydii, 12 μg ml−1 for E. dermatiditis and 6 μg ml−1 for G. argillacea. VRC was the most active drug in combination without any antagonism with the exception of few P. boydii isolates. COL as single agent and in most combinations with antifungals exhibits in vitro antifungal activity against filamentous ascomycetes occurring in cystic fibrosis patients and may offer a novel therapeutic option, especially for multidrug‐resistant S. prolificans.